Label Halal, Brand Image, dan Reference Group: Dampak Terhadap Keputusan Pembelian Muslim Pada Produk Perawatan Kulit Di Marketplace Shopee - Fertika Eliza; Lina Marlina; Elis Nurhasanah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The purpose of this study was to determine the impact of halal labels, brand image, and reference groups on Muslim consumers' purchasing decisions on skincare products in the Shopee marketplace, either partially or simultaneously. Using descriptive quantitative methods, with a sample of 100, through a questionnaire and using SPSS 25 to analyze. The results of the research show that: 1) Halal labels have a positive and significant influence on purchasing decisions with a coefficient of determination of 34.5%; 2) Brand Image has a positive and significant influence on purchasing decisions with a coefficient of determination of 37.4%; 3) Halal label has a positive and significant influence on purchasing decisions with a coefficient of determination of 30.4%; 4) Halal label, brand image, and reference group have an influence on purchasing decisions with an R square value of 55.3%. Halal label, brand images, and reference groups have an impact on Muslim consumers' purchasing decisions on skincare products in the Shopee marketplace, either partially or simultaneously. In this case, it means that all hypotheses are accepted.